Antibacterial effect of ethanolic Gnetum gnemon L. leaf extract on food-borne pathogens and its application as a natural preservative on raw quail eggs - Trisha, Mansura Rahman; Deavyndra Gunawan, Vyenna; Wong, Jun Xian; Pak Dek, Mohd Sabri; Rukayadi, Yaya (Elsevier, 2024)
Gnetum gnemon L. is an evergreen tree that belongs to the Gnetaceae family and is commonly used as a vegetable and medicinal plant among indigenous people. The key goal of this study was to assess the antibacterial efficacy of ethanolic G. gnemon leaf extract (EGLE) against six food-borne pathogens. The antimicrobial activity of EGLE was evaluated using multiple methods, including the well diffusion assay (WDA), minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and time-kill assay. Gas Chromatography-Mass Spectrometry (GC-MS) analysis was used to identify active volatile compounds responsible for EGLE's antibacterial activities. Total plate count (TPC) was conducted to measure microbial populations and evaluate the efficacy of EGLE as a natural preservative in raw quail eggs. 100 g of dried and powdered sample yielded an average of 11.58 ± 0.38 % post-extraction. The inhibition zone in WDA ranged from 11.00 ± 0.57–13.50 ± 0.58 mm, MIC ranged from 6.25 to 50.00 mg/mL, and MBC values were between 12.5 and >50 mg/mL. Results from the time-kill study showed that at 4 × MIC Bacillus pumilus and B. megaterium were completely killed in 1 h incubation time and other bacteria were killed within 2–4 h. Findings from TPC demonstrated that at the highest tested concentration of EGLE, there was no significant bacterial growth for a 30-day observation period. Thereby, suggesting that it had the potential to function as a natural preservative for raw quail eggs. EGLE may be a viable alternative to synthetic preservatives in combating food-borne pathogens. © 2024 The Authors